2021
DOI: 10.3390/machines10010028
|View full text |Cite
|
Sign up to set email alerts
|

Blending Colored and Depth CNN Pipelines in an Ensemble Learning Classification Approach for Warehouse Application Using Synthetic and Real Data

Abstract: Electric companies face flow control and inventory obstacles such as reliability, outlays, and time-consuming tasks. Convolutional Neural Networks (CNNs) combined with computational vision approaches can process image classification in warehouse management applications to tackle this problem. This study uses synthetic and real images applied to CNNs to deal with classification of inventory items. The results are compared to seek the neural networks that better suit this application. The methodology consists of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…In paper [18], it was shown that it is possible to recognise knife-type hand-held weapons carried by armed individuals from digital images with an accuracy of 87%. Study [19] used synthetic and real images applied to CNNs to classify warehouse items. The AI model was based on a combination of DenseNet and Resnet pipelines for colour and depth images and proved outperformance in terms of accuracy and precision rates compared to single CNNs, achieving a 95.23% accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…In paper [18], it was shown that it is possible to recognise knife-type hand-held weapons carried by armed individuals from digital images with an accuracy of 87%. Study [19] used synthetic and real images applied to CNNs to classify warehouse items. The AI model was based on a combination of DenseNet and Resnet pipelines for colour and depth images and proved outperformance in terms of accuracy and precision rates compared to single CNNs, achieving a 95.23% accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Convolution neural network (CNN), a deep neural network among many deep neural networks, is very popular because of its sparse connection and weight-sharing feature [21]. Notably, CNNs [22,23] have brought many significant breakthroughs in image recognition. Inspired by CNNs in image recognition, Ronneberge et al [24] proposed a fully convolutional neural network, U-Net, with an encoder-decoder architecture for medical image segmentation.…”
Section: Introductionmentioning
confidence: 99%